ORIGIN AND DISTRIBUTION OF BIOMARKERS IN THE SULPHUR RICH UTRILLAS COAL BASIN - TERUEL MINING DISTRICT - SPAIN - Olivella M.A.; Gorchs R.; de las Heras F.X.C. (My University, 2006)
The Utrillas coal facies are located in the Maestrazgo basin in NE Spain. This mining district of Teruel contains sub-bituminous deposits from the Middle Albian (Lower Cretaceous 105 Ma) in areas near a delta estuary with abundant sulphur. The high sulphur content is due to an influx of sulphate caused by the geological recycling of Triassic gypsum from the catchment area into the delta estuary. In some outcrops, the weathered coal reveals leonardite deposits. The depositional environment of the basin originated coals, some of which are currently mined. The organic matter of the coals has been the object of scattered reports. Studies have focused on bulk pyrolysis parameters and microscopic observation in Utrillas samples, as well as the inorganic and insoluble organic fraction. We analysed the organic soluble extract of the Utrillas coals using GC-MS in order to characterize their aliphatic, aromatic and organosulphur compounds. The biomarker distribution allowed us to recognize different inputs, assess their depositional palaeoenvironment and finally determine their degree of maturity. In particular, homologous series of hopanes related to eubacteria were present. Biomarkers characteristic of higher plant inputs were also widely distributed (e.g. phyllocladane or C29 steranes). The presence of linear alkylbenzenes allowed us to recognize the palaeodepositional reducing environments where they were deposited. Specifically, thienylhopanes were associated with sulphur-reducing environments. Finally, the abundance of unsaturated biomarkers such as diacholestenes indicated low-maturity coals. Various aromatic ratios such as the methylphenanthrene index also suggested diagenesis in the initial stage. © 2006 Elsevier Ltd. All rights reserved.
Keywords: Triassic; Albian; Mesozoic::Triassic; Мезозой::Триасовая; Mesozoic::Cretaceous::Lower::Albian; Мезозой::Меловая::Нижний::Альбский